Sequence-dependent structural variations of hammerhead RNA enzymes. - Heus, H A (1990)
The discovery of in vivo catalytic activity for the hammerhead RNA self-cleaving domain has led to the development of a new class of sequence-specific RNA endonucleases. Two such ribozymes have been synthesized using in vitro transcription with T7 polymerase and their structures have been studied by optical spectroscopy, nuclear magnetic resonance and nondenaturing gel electrophoresis. These data show the presence of a stable hairpin consisting of a double helical stem and a tetranucleotide loop in both RNA enzymes. Additional structure, with different stabilities, is also observed in both RNA enzymes. The half-lives for cleavage of the complementary RNA substrates by these two RNA enzymes have been previously shown to differ by a factor of 50. The data presented here suggest that this rate difference may be a result of the formation of catalytically inactive conformations in the RNA enzyme which interfere with formation of the enzyme-substrate complex.